SE adjustment of planar mesh screen by fine‐tuning metal thickness. Issue 4 (12th April 2018) - Corredores, Yonathan; Castel, Xavier; Besnier, Philippe; Dupeyrat, Cyril; Foutrel, Patrice
Abstract : The study presents the thickness effect of mesh metal films printed onto glass substrate on the shielding effectiveness (SE) of such transparent screens. Currently, standards in microelectronic technology use a metal film thickness of between ∼100 nm and few micrometres, depending on the available deposition and implementation techniques. This study demonstrates that the thickness of mesh metal films is a key parameter which needs to be adjusted precisely. A theoretical model based on SE, complex impedance and optical transparency has been developed for this purpose. At microwaves, a relevant selection of the metal thickness values from 0.1 to 2 µm changes the SE at low frequency (from 36 to 40 dB at 2 GHz, respectively) while maintaining it constantly at a higher frequency (close to 20 dB at 18 GHz). The optical transparency of such mesh screens is kept constant over the entire visible light spectrum (78%). Experimental data are in complete agreement with the theoretical values.